The Influence of Leadership and Work Environment on Job Satisfaction of Delia General Hospital Employees - Manuel Triyanta Tarigan; Rifky Budi Setiawan; Juniarti (Yayasan Multidimensi Kreatif, 2024)
Employee job satisfaction is the main focus of every company. Basically, job satisfaction is not just a feeling of pleasure or satisfaction for the work done, but rather the result of a thorough experience in the work environment. This study aims to analyze and get answers to whether leadership variables and work environment have a partial and simultaneous effect on job satisfaction of Delia General Hospital employees. This study used an associative approach where the number of respondents was 65 people. The test was carried out using SPSS ver 26. The results showed that under leadership (X1) had no effect and was significant on job satisfaction (Y) while the work environment (X2) had a positive and significant effect on job satisfaction. Then leadership (X1) and work environment (X2) have a silmultan effect on job satisfaction (Y).